EVALUATION OF THE ANTIMICROBIAL ACTIVITY OF CRUDE HERBAL EXTRACTS AGAINST DIFFERENT MICROORGANISMS - G. D. RAM; D. K. VERMA; INDRA YADAV (The Bioscan, 2012)
Antimicrobial activity of extracts of four plants viz., Ocimum tenuiflorum, Emblica officinalis, Coriandrum sativum and Azadirachta indica were evaluated against four microorganisms viz., Escherichia coli, B. amyloliquifaciens, Staphylococcus aureus and Pseudomonas aeruginosa. The extract of Ocimum tenuiflorum was found to be active in all three concentrations (25, 50 and 75 μg/μL) against E. coli, two concentrations (50 and 75 μg/μL) against P. aeruginosa and S. aurius. Emblica officinalis was effective against almost all three concentrations of all microorganisms except 25 μg/μL of S. aurius. Coriandrum sativum showed the maximum zone of inhibition against S. aurius (26 mm) and. P. aeruginosa (16 mm). Azadirachta indica showed best effect against P. aeruginosa (MZI-16mm), and to some extent against E. coli and S. aurius.